SOCIALIZATION AND ASSISTANCE OF THE HEALTHY LIVING COMMUNITY MOVEMENT PROGRAM FOR HEALTH CADRES AND DIABETES MELLITUS SUFFERERS IN THE in the PURBARATU PUSKESMAS AREA, TASIKMALAYA CITY - Asep Riyana Asep Riyana; Unang Arifin Hidayat Unang Arifin hidayat; Dudi Hartono Dudi Hartono; Asep Kuswandi Asep Kuswandi; Arip Rahman Arip Rahman (LP4M STIKes Karsa Husada Garut, 2024)
The Healthy Living Community Movement (GERMAS) is a systematic and planned action carried out jointly by all components of the nation with awareness, willingness and ability to behave healthily to improve the quality of life. The implementation of GERMAS must start from the family, because the family is the smallest part of society that forms personality. GERMAS can be done by: Doing physical activity, consuming vegetables and fruit, not smoking, not consuming alcohol, checking your health regularly, cleaning the environment, and using a toilet. In the initial stage, GERMAS nationally started by focusing on three activities, namely: 1) Carrying out 30 minutes of physical activity per day, 2) Consuming fruit and vegetables; and 3) Check your health regularly. GERMAS is a national movement initiated by the President of the Republic of Indonesia which prioritizes promotive and preventive efforts, without neglecting curative-rehabilitative efforts by involving all components of the nation in promoting the healthy paradigm. To make GERMAS a success, you cannot only rely on the role of the health sector alone. The aim of this community service activity is to socialize the program that has been created by the government so that good habits can be achieved in society with healthy community living habits. Local Community Health Center... Based on this, the DIII Nursing Study Program feels it is necessary to socialize the Community Healthy Living Movement by carrying out regional guidance, especially for health cadres and DM patients in the Purbaratu Community Health Center Area, Tasikmalaya City.